"Ninjinto" (Ginseng Decoction), a Traditional Japanese Herbal Medicine, Improves Gastrointestinal Symptoms and Immune Competence in Patients with Chronic Intestinal Failure. (1st October 2015) - Uehara, Shuichiro; Ogawa, Keiko; Arimitsu, Junsuke; Okuyama, Hiroomi
Abstract : Background . Treating functional gastrointestinal disorders is extremely difficult. We herein report the effect of the oral administration of Ninjinto (NJT, ginseng decoction), a traditional Japanese Kampo medicine, on chronic intestinal failure. Patients and Methods . Seven patients with chronic intestinal failure treated with NJT were evaluated in this study. The primary diseases included chronic intestinal pseudoobstruction (CIPO:n = 4 ), short bowel syndrome (SBS:n = 2 ), and intestinal atresian = 1 . All patients orally received NJT extract granules at a dose of 0.3 g/kg BW per day. The treatment outcomes were then assessed according to the patients' symptoms and consecutive abdominal X-ray findings. Results . The targeted symptoms were abdominal distension in four patients, diarrhea in three patients, and frequent hospitalization due to infections in two patients. An improvement in the symptoms was observed in six of the seven patients, whereas one patient with SBS did not show any improvement. An improvement in an abdominal roentgenogram was observed in the four patients with remarkably dilated bowel loops due to CIPO. Conclusions . NJT may be effective in controlling functional gastrointestinal disorders associated with chronic intestinal failure. The use of Kampo medicine in the field of pediatric surgery may help to improve the quality of life in children suffering from such conditions.